The transmission of monetary and technology shocks in the euro area - Alves, Nuno (2022)
We build structural VARs for the euro area to analyze the responses of a set of euro area macroeconomic variables to monetary policy and technology shocks. We then test their robustness to different specifications of hours worked, sample periods and the definition of the variables used. We conclude that while the responses to monetary policy shocks appear to be broadly robust, the responses to technology shocks crucially depend on whether hours worked are introduced in levels or in first differences.